Girls’ Vulnerability in Child-Marriage - Maria Ulfah Anshor (Jurnal Perempuan, 2016)
Child marriage was primarily caused by Law No 1 1974 Marriage that stated girls could be marriage at the age of 16. The rejection of the judicial review of this Law and other severe factors has increased the number of child-marriage in Indonesia. Social change behavior will not solve the problems of child marriage. Status of girls in child-marriage are as follows: girls are vulnerable to being divorced, girls are prone to domestic violence, girls are prone to sexual violence and victim of phedophilia, girls are prone to drop-out from education and having poor and low access in jobmarket. There is an urgent need to a systemiv advocacy to end child marriage.